Determinación del coeficiente de rendimiento de la especie Hura crepitans (catahua) en el proceso de transformación de madera en troza a madera aserrada en la empresa Inversiones W&A, Loreto- Maynas - Iquitos - 2022 - López Bernal, Saúl Alexander (2023)
This study was carried out in the wood transformation plant of the company Inversiones W&A, in order to determine the performance of the species Hura crepitans (Catahua) in the process of transforming wood into logs. From the results obtained, it is found that 57 lgs of Hura crepitans (Catahua) wood were used with a total volumen of 212,997 m?, being 57 first quality logs 180.68 m? and 10 second quality logs with 32,317 m?. Of the total wood obtained after the sawing process, 6,809 pieces were obtained with 72,071 pt (212.99 m?) equivalent to 80% in the yield of the raw material and sawn wood ratio. In the relation between sawn wood and wood by category, a yield of 72.80% was obtained for commercial long wood, 24.50% for narrow long wood and 2.71% for rejected wood. The alternative hypothesis is accepted since there is a close relationship between the yield in volumen and typology of the sawn wood of the Hura crepitans (catahua) species and the quality of the logs (ha).